Pengaruh Good Corporate Governance dan Konservatisme Akuntansi Terhadap Tax Avoidance (Studi Pada Perusahaan Badan Usaha Milik Negara yang Terdaftar di Bursa Efek Indonesia periode 2017-2021) - Priatiningsih, Dian; Syafnita , Syafnita; Mardayanti, Mella; Sari, Fangela Myas; M. Trihudiyatmanto (Indonesian Journal Publisher, 2024)
The purpose of this research is to analyze Good Corporate Governance and Accounting Conservatism on Tax Avoidance (A Study on State-Owned Enterprises Listed on the Indonesia Stock Exchange in the Period 2017-2021). This research aims to verify the factors that impact the level of tax avoidance. The independent factors tested in this research include independent commissioners, audit committees, institutional ownership, and accounting conservatism. The dependent variable used is tax avoidance, which is measured using the cash effective tax rate (CETR). The research subjects consist of 8 state-owned enterprises (SOEs) listed on the Indonesia Stock Exchange (IDX) during the period of 2017-2021. The observation was conducted over 5 years. Purposive sampling method was used to select research samples, taking 40 samples based on specific criteria. The collected data was then analyzed using multiple linear regression model using SPSS software version 22. This research has been well designed, but the results of this research still have shortcomings and limitations so that further research is expected to use other methods such as the interview method to obtain honesty in respondents' answers, and the object can be further expanded. The results of this research indicate that independent commissioners and institutional ownership have no significant influence on tax avoidance, while audit committees and accounting conservatism have a negative influence on tax avoidance.